Ilmu Munasabah Ayat: Menyikapi Keterkaitan antar Ayat dalam Al-Qur'an - Arinda Rahmi Auliani; Zaskia Berliana Zulfa; Ihsan Azhar; Gita Oktaviona4; Ani Marlia (PT. Pustaka Cendekia Publisher, 2025)
Munasabah science is a branch of science in the Quran that examines the relationship and harmony between the poetry of the text and the surahs. Because the structure of the Quran is not chronological, but rather specific wisdom and insight, research on Munasabaayat is important for understanding God's perfect and profound message. The purpose of this study is to test systematic methods for addressing the relationships between verses to avoid misunderstandings when interpreting the verses of the Quran. Using a qualitative approach and literature review, this study demonstrates that Munasabaayat not only highlights the beauty of the Quran's linguistic structure but also strengthens understanding of its themes and context-related interpretations. Awareness of the connections between verses also helps build the integrity of understanding Islamic teachings. Therefore, the science of Munasaba is an important tool for maintaining the credibility and consistency of the Quran's importance in topics of intersection and cross-referencing.